(untitled) (Margalla Papers, 2023)
Land warfare has remained a prominent factor in international politics. States have been developing strategies on operational and tactical levels to strengthen their land defence forces. Christopher Tuck's book, Understanding Land Warfare, is a comprehensive addition to the existing academic literature focusing on historical and changing contemporary land warfare concepts. The book is divided into three parts that contain eleven chapters. Part I, The Development of Land Warfare, underlines modern land warfare's fundamental concepts and historical development since 1900. Part II, What is Victory? highlights political and military gains in unconventional, low-intensity asymmetric warfare, including counterinsurgency operations, peace operations and hybrid warfare. Part III, The Future, explores possible developments in land warfare techniques while using Russia and China as case studies.